MODEL PENGEMBANGAN KURIKULUM PAI YANG RELEVAN DAN INOVATIF - Maharani, Dewi (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
The development of the Islamic Education Curriculum (PAI) is a strategic step to address the increasingly complex global challenges. This article is motivated by the urgent need for a PAI curriculum that is not only relevant to Islamic values but also adaptable to the advancements of the modern era, such as cultural diversity and technological progress. Various curriculum development models, including competency-based, multicultural, and technology-driven approaches, are the main focus of discussion to provide innovative solutions in Islamic education. This study employs a qualitative descriptive method based on literature reviews. Data sources include relevant journals, books, and academic documents. The analysis aims to identify fundamental principles, relevant development models, and challenges and solutions in implementing the PAI curriculum across different educational levels. The findings reveal that competency-based curriculum models emphasize students' skills and capabilities to face global challenges. The multicultural approach highlights harmony in diversity, while technology integration supports more effective and efficient learning. This study underscores the importance of a holistic approach that integrates theory and practice to produce a curriculum that is relevant, innovative, and applicable. This article is expected to serve as a reference for educators, policymakers, and Islamic educational institutions in designing impactful curricula capable of shaping intellectually, spiritually, and socially competent generations.